Local wisdom of the people of Rengel village in maintaining environmental sustainability in the Ngerong Cave ecotourism area - Avivi Nur Aina; Imas Cintamulya (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The condition of environmental sustainability in Indonesia is decreasing along with the times. People tend to focus on function without thinking about how to preserve nature. Ngerong Cave is one of the uses of nature as a tourist attraction and an area for meeting the needs of the people of Rengel Village, Tuban. The utilization of the Ngerong Cave creates new problems, such as the amount of garbage and detergent waste that pollutes the Ngerong aquatic environment. Utilizing nature without paying attention to environmental conditions will harm environmental sustainability if it occurs continuously. Therefore, efforts need to be made to maintain an integrated and sustainable environment. This effort can be done by applying the local cultural values of the community. Internalization of local cultural values can build public awareness of environmental conservation awareness. This research is descriptive qualitative and quantitative research. This study aims to explain the relevance of local cultural values to environmental sustainability which is supported by empirical data in the form of the abundance of aquatic biota in Ngerong Cave and plant diversity in Ngerong Cave and direct observations related to environmental conditions. The results of the study conclude that the internalization of local cultural values affects ecological sustainability in the Ngerong Cave area.